LIMITATIONS AND CONTRADICTIONS IN THE FORMATION OF HUMAN CAPITAL IN RURAL AREAS OF UKRAINE (Development Service Industry Management, 2024)
The article is devoted to generalizing limitations and contradictions regarding human capital formation in rural areas. The dominance of factors contributing to rural unemployment is emphasized. The labor market is characterized by a surplus of labor over demand due to the reduction of agricultural production and the social sphere, the orientation of enterprises towards labor intensification, which leads to the aggravation of the employment problem. Agribusiness remains the largest employer, creating a monopsony in the labor market that causes low wages and encourages migration to cities. The non-competitive structure of the labor market hurts agriculture and peasants' standard of living. The need to diversify the rural economy by developing non-agricultural activities, such as green tourism, handicrafts, and household services, is emphasized. Measures to stimulate these activities are proposed, particularly at the legislative and governmental levels. The importance of local community initiatives in implementing projects that can improve the economic situation in the village has been determined. The impact of urbanization on the formation of human capital in rural areas of Ukraine is summarized. Urbanization causes an outflow of population to cities, negatively affecting rural regions. The leading causes of this process are named industrialization, commerce, labor market, modernization, and social aspects. It is proposed that social infrastructure and transport links be improved, non-agricultural activities be developed, and village life be popularized through media and education. It is substantiated that the factors that prevent the formation of human capital in rural areas of Ukraine are low-quality school education, poor medical care, unsatisfactory level of development of social infrastructure, increasing rural unemployment, monopsony of agricultural enterprises in the rural labor market, low level of development of non-agricultural types of business, urbanization.
Keywords: human capital; rural population; rural areas; urbanization; diversification; agrarian sector of the economy